1999
DOI: 10.1136/gut.45.6.864
|View full text |Cite
|
Sign up to set email alerts
|

Role of inducible nitric oxide synthase in trinitrobenzene sulphonic acid induced colitis in mice

Abstract: Background-Studies using inhibitors of nitric oxide synthase (NOS) to date are inconclusive regarding the role of inducible NOS (iNOS) in intestinal inflammation. Aims-(1) To examine the role of iNOS in the development of chronic intestinal inflammation; (2) to identify the cellular source(s) of iNOS. Methods-Colitis was induced by an intrarectal instillation of trinitrobenzene sulphonic acid (TNBS, 60 mg/ml, 30% ethanol), in wild type (control) or iNOS deficient mice. Mice were studied over 14 days; the colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
3
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 42 publications
9
114
3
3
Order By: Relevance
“…Our findings are similar to those seen in collagenous colitis (41), where high iNOS expression by intestinal epithelial cells is not associated with overt mucosal tissue damage. In fact, like McCafferty et al (34,35) we found that iNOS KO mice exhibited a more severe and protracted colitis, suggesting that rather than acting as a noxious substance during inflammation, NO may have beneficial actions. The absence of iNOS expression under control conditions suggests that iNOS plays its beneficial role after the induction of colitis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our findings are similar to those seen in collagenous colitis (41), where high iNOS expression by intestinal epithelial cells is not associated with overt mucosal tissue damage. In fact, like McCafferty et al (34,35) we found that iNOS KO mice exhibited a more severe and protracted colitis, suggesting that rather than acting as a noxious substance during inflammation, NO may have beneficial actions. The absence of iNOS expression under control conditions suggests that iNOS plays its beneficial role after the induction of colitis.…”
Section: Discussionmentioning
confidence: 61%
“…These limitations have encouraged the study of colitis in mice genetically deficient in iNOS. Unfortunately, these studies (34,35,62) have utilized different protocols and yielded conflicting results. Moreover, the few studies that have examined the roles of the other NOS isoforms in experimental colitis have also been conflicting; such that it remains unclear whether the eNOS and nNOS isoforms contribute to intestinal inflammation (2,16) or whether they instead maintain intestinal homeostasis and mucosal integrity (5,48).…”
mentioning
confidence: 99%
“…Previous studies have consistently found that the loss of iNOS causes reduced severity of DSS-induced colitis. 13,35,36 However, studies that involve the use of iNOS inhibitors have generated mixed information, with the inconsistencies largely stemming from the narrow window of selectivity and specificity toward iNOS of these inhibitors. 14,15 Exogenous NO-donors stimulate electrolyte secretion in guinea pig mucosa, but with the role of endogenous NO largely undetermined.…”
Section: Inhibition Of Cftr and Inos Activity Attenuates Diarrhea In mentioning
confidence: 99%
“…To induce colitis, 200 mg/kg TNBS (Sigma-Aldrich) dissolved in 30% ethanol was administered intrarectally to lightly anesthetized (ketamine/ xylazine) mice via a catheter (20). Control mice received 30% ethanol.…”
Section: Tnbs-induced Colitismentioning
confidence: 99%